Knowledge of High School Students and Parents about Adolescent Reproductive Health - Ulfa Maihadi Putri; Elsa Yuniarti; Sa'adiyatul Fuadiyah; Rahmawati D Rahmawati D (ATRIUM PENDIDIKAN BIOLOGI, 2020)
Students of SMAN 1 Batang Anai have knowledge about adolescent reproductive health as limited as bathing regularly, exchanging panties after taking a shower and for young women swapping pads 3 times a day. The results of interviews with counseling teachers that there had been cases of pre-marital pregnancy and the presence of same-sex students. The purpose of this study is to describe the knowledge of high school students and parents about the reproductive health of adolescents at SMAN 1 Batang Anai. This research is a descriptive study with a population of 118 students and 24 parents of students determined by propotinate stratified random sampling, the measuring instrument used is a question as an instrument. Analysis In this study using simple regression analysis and path analysis. The results of the study found that students 'knowledge included in the sufficient category with a total of 82 people (69.5%), age and sex of students had an influence on students' knowledge of reproductive health with a influence of 3.3% and 4.2% respectively. . Likewise, the knowledge of parents is included in the category of enough with 12 people (50%), the level of education of parents influences the knowledge of parents about adolescent reproductive health with a large influence of 60.7%. Knowledge of parents is very influential on children's knowledge about adolescent reproductive health with a large influence of 58.1%.